Using dynamic measurements to detect and locate ruptured cables on a tensegrity structure. (15th October 2018) - Sychterz, Ann C.; Smith, Ian F.C.
Highlights: Methods applied to structure during deployment and in-service conditions. Using changes in natural frequencies for successful detection of damaged elements. Moving window PCA successfully identified elements adjacent to damage. Error-domain model falsification successfully identified region of damaged element. Abstract: Tensegrity structures are cable-strut systems held in equilibrium due to self-stress. There is potential for damage tolerance when they are kinematically redundant. In this paper, detection and location of a ruptured cable in a deployable tensegrity footbridge are studied through monitoring changes in dynamic behavior. Position values and axial load values of elements are measured before, during, and after a cable breakage. Free and forced-vibration-induced dynamic behavior of the tensegrity structure are characterized in the state of deployment (one half of the structure) and in-service (full structure). Examination of ambient vibrations for the half structure and forced vibrations for the full structure successfully led to detection of ruptured cables. Exclusion of possible damage cases for location using measurements effectively reduces the number of candidate cases when using nodal displacement measurements. Correlation methods using strain measurements are also successful to locate a ruptured cable. These methods reveal the potential for self-diagnosis of complex sensed structures.